Key advances in clinical informatics transforming health care through health information technology - Sheikh, Aziz; Wright, Adam; Cresswell, Kathrin M.; Bates, David W. (Elsevier, 2017)
Key Advances in Clinical Informatics: Transforming Health Care through Health Information Technology provides a state-of-the-art overview of the most current subjects in clinical informatics. Leading international authorities write short, accessible, well-referenced chapters which bring readers up-to-date with key developments and likely future advances in the relevant subject areas. This book encompasses topics such as inpatient and outpatient clinical information systems, clinical decision support systems, health information technology, genomics, mobile health, telehealth and cloud-based computing. Additionally, it discusses privacy, confidentiality and security required for health data. Edited by internationally recognized authorities in the field of clinical informatics, the book is a valuable resource for medical/nursing students, clinical informaticists, clinicians in training, practicing clinicians and allied health professionals with an interest in health informatics